Analysis of phellinus igniarius effects on gastric cancer cells by atomic force microscopy. (January 2023) - Wang, Jia-He; Wang, Jia-Jia; Ju, Tuo-Yu; Huang, Yu-Xi; Yuan, Li-Xin; Luo, Ying-Hui; Chen, Yu-Juan; Wang, Zuo-Bin
Abstract: Gastric cancer is one of the common malignant tumors in the world, which originates from the gene mutation of human cells. In this work, an atomic force microscope was used to quantitatively detect the changes of multiple physical parameters such as the cell morphology, surface roughness, elasticity modulus and adhesion force before and after Phellinus linteus stimulation. The experimental results show that Phellinus linteus can change the shape of gastric cancer cells (SGC-7901) from flat to spherical, and increase their height and surface roughness values. The adhesion force of cells is reduced and the elasticity modulus is increased. But there are no significant differences in the morphology and mechanical properties of gastric epithelial cells (GES-1). The results indicate that Phellinus linteus has a high anticancer effect on the gastric cancer cells, but has less toxic side effects on the gastric epithelial cells. This work proves that Phellinus linteus can be used as a preferred anticancer drug for the treatment of gastric cancer cells. Graphical abstract: Home-made Atomic Force Microscope. ga1